1983
DOI: 10.1055/s-2007-1018803
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronamine - A Beta-adrenergic Metabolite of Triiodothyronine?

Abstract: Triiodothyronamine (Triam) is a potential metabolite of triidothyronine (T3), resulting from decarboxylation of the side-chain. In an attempt to elucidate the physiological properties of Triam we have investigated the binding of Triam to beta-adrenergic receptors, using turkey-erythrocytes and performing binding studies with ( (-)(3H)-dihydroalprenolol) ( (-)(3H)-DHA) as a specific beta-adrenergic ligand. The inhibition constant Ki for Triam was determined as 5 X 10(-6) M, compared to dopamine (Ki = 1,3 X 10(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Interestingly, an antagonistic effect on β-adrenergic signaling was reported in the early 80′s for several thyronamines. T 3 AM, 3,5-T2AM, and T 0 AM interfere with ligand binding to adrenergic receptors expressed at the plasma membrane of turkey erythrocytes and inhibited the activation of cAMP synthesis [83], [84]. Of special note, octopamine acts as an orthosteric ligand for ADRB1 and is an ADRB2-antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an antagonistic effect on β-adrenergic signaling was reported in the early 80′s for several thyronamines. T 3 AM, 3,5-T2AM, and T 0 AM interfere with ligand binding to adrenergic receptors expressed at the plasma membrane of turkey erythrocytes and inhibited the activation of cAMP synthesis [83], [84]. Of special note, octopamine acts as an orthosteric ligand for ADRB1 and is an ADRB2-antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Early investigations performed in turkey erythrocytes reported that T 3 AM, T 2 AM, and T 0 AM displaced dihydroalprenolol, a specific b 2 -adrenergic ligand, with a Ki in the micromolar range [17]. In partial contrast to these findings, no change in cAMP was produced in HEK-293 cells expressing either the dopamine D 1 receptor or the b 2 -adrenergic receptor, by treatment with T 0 AM or T 1 AM at concentrations as high as 10 lM [4].…”
Section: T 1 Am Receptorsmentioning
confidence: 99%
“…This has subsequently been verified by numerous laboratories (Mühlhaus et al, 2014;Cöster et al, 2015;Chiellini et al, 2017), with 3IT also shown to act as an agonist at TAAR2 (Babusyte et al, 2013;Cichero and Tonelli, 2017) and as an inverse agonist at TAAR5 (Dinter et al, 2015c). 3IT is promiscuous, however, and also interacts with high affinity at a 2 -adrenoceptors (Regard et al, 2007;Dinter et al, 2015b), b-adrenergic receptors (Meyer and Hesch, 1983;Kleinau et al, 2011;Dinter et al, 2015a), muscarinic acetylcholine receptors (Laurino et al, 2016), transient receptor potential cation channel subfamily M member 8 ion channels (Khajavi et al, 2015;Lucius et al, 2016), various monoamine and organic anion transporters (Snead et al, 2007;Panas et al, 2010), and molecular target(s) within mitochondria, including the F 1 -F 0 ATP synthase (Cumero et al, 2012) and possibly complex III (Venditti et al, 2011). 3IT also tightly binds to the plasma protein apolipoprotein B-100 .…”
Section: E 3-iodothyronaminementioning
confidence: 99%